Gestion des risques et des crises, entre gouvernance de la sécurité et gouvernance territoriale. Ce que la résilience change (ou pas) en Île-de-France - Magali Reghezza-Zitt; Ihnji Jon (L'Espace Politique)
This article documents the introduction of ‘resilience’ to the French model of risk governance, and examines how this concept has been operationalized in risk and security governance as well as territorial governance in Parisian region. The article is based on qualitative approach, relying on formal interviews, participant and non-participant observation, regular informal exchanges with certain stakeholders and the analysis of gray literature documents (e.g. government reports, policy statements, and other technical reports). It first discusses the structural characteristics of risk governance in Île-de-France, underlining its territorial fragmentation and intricate matrices of actors in different levels of government that further aggravate the complexity of the already fragmented governance model. We then explore how the concept of resilience becomes operationalized in such context, based on our key informant interviews with practitioners in the field. Our investigation has revealed that, while the introduction of resilience does not necessarily imply significant changes in the practices of disaster management, the concept has served a role in reorganization of risk and security governance — via accompanying the restructuring of territorial governance which has been under way for several years. Furthermore, it has been observed that the concept is also of service to pushing through some of the existing political agendas and policy initiatives; this implies that the operationalization of ‘resilience’ largely relies on the performativity of the concept that only gets developed by the actual use of practitioners.